The challenge of mapping the human connectome based on diffusion tractography. Issue 1 (December 2017) - Maier-Hein, Klaus; Neher, Peter; Houde, Jean-Christophe; Côté, Marc-Alexandre; Garyfallidis, Eleftherios; Zhong, Jidan; Chamberland, Maxime; Yeh, Fang-Cheng; Lin, Ying-Chia; Ji, Qing; Reddick, Wilburn; Glass, John; et al.
Abstract Tractography based on non-invasive diffusion imaging is central to the study of human brain connectivity. To date, the approach has not been systematically validated in ground truth studies. Based on a simulated human brain data set with ground truth tracts, we organized an open international tractography challenge, which resulted in 96 distinct submissions from 20 research groups. Here, we report the encouraging finding that most state-of-the-art algorithms produce tractograms containing 90% of the ground truth bundles (to at least some extent). However, the same tractograms contain many more invalid than valid bundles, and half of these invalid bundles occur systematically across research groups. Taken together, our results demonstrate and confirm fundamental ambiguities inherent in tract reconstruction based on orientation information alone, which need to be considered when interpreting tractography and connectivity results. Our approach provides a novel framework for estimating reliability of tractography and encourages innovation to address its current limitations. Though tractography is widely used, it has not been systematically validated. Here, authors report results from 20 groups showing that many tractography algorithms produce both valid and invalid bundles.